The Correlation between Maternal Beliefs about Children’s Play and Children’s Play Preferences Based on Maternal Educational Background in Jember Regency - Putri, Marisa; Yuli Kurniawati Sugiyo Pranoto; Liftiah Liftiah (JURNAL PENDIDIKAN USIA DINI, 2025)
Parental beliefs have a valuable influence on children’s play and learning experiences at home. This study aimed to analyze the correlation between maternal beliefs about children’s play, children’s play preferences, and maternal educational background as a variable that controlled both aspects. The respondents of this study were 125 mothers of children aged 5-6 years in Jember (49% boys and 51% girls). Data were analyzed using the partial correlation method to measure the correlation between these variables. The results showed that maternal beliefs had a very weak and insignificant correlation with children’s play preferences, with a correlation value of 0.073 and a significance (2-tailed) of 0.422 (p>0.05). Maternal education background had a weak but significant correlation with maternal beliefs (correlation = 0.207; significance = 0.021) (p<0.05), and maternal education background had a low and insignificant correlation with children’s play preferences (correlation = 0.076; significance = 0.401). In addition, it was found that when the maternal education background was controlled, maternal beliefs had a very weak correlation with children’s play preferences. So, the maternal education background is not a controlling variable that influences this correlation (correlation = 0.058; significance = 0.520). This finding indicates that maternal education background is not the primary variable that has a relationship in shaping maternal beliefs about children’s play and children’s play preferences in early childhood. This finding emphasizes children’s academics, even though mothers understand the value of play.